APPLICATION OF LEARNING MODEL PROBLEM BASED LEARNING IN NATURAL AND SOCIAL SCIENCE SUBJECTS TO IMPROVE THE LEARNING OUTCOMES ELEMENTARY STUDENTS - Deka Zulysa; Muhammad Dhori (STKIP Citra Bakti, 2026)
The low learning outcomes of fourth-grade science students at MI Al-Azhar Muara Pinang was the main driver of this research, which highlighted the need for more creative teaching methods. The goal of this project is to use the Problem Based Learning paradigm to improve student engagement and learning outcomes. Classroom Action Research, which is carried out in two cycles with the planning, implementation, observation, and reflection phases, is the type of research used. Fourteen fourth-grade students were made the subjects of the study. Multiple-choice learning outcome exams and observation of student activities were used as data collection methods, and qualitative and quantitative descriptive data analysis was carried out. Through problem-solving-based exercises that actively engage students in group projects, presentations, and conversations, the Problem-Based Learning approach is implemented. With a completion rate of 92.8%, the research findings show an increase in student learning outcomes. This shows that problem-based learning approaches are successful in improving student engagement and learning outcomes.